Расчет магнитного поля трехфазных кабельных линий при двустороннем замыкании собственных экранов кабелей, охваченных ферромагнитными сердечниками - Розов, В.Ю.; Гринченко, В.С.; Ткаченко, А.О. (Електротехніка і електромеханіка, 2017)
Получены компактные соотношения для расчета эффективности экранирования магнитного поля высоковольтной трехфазной кабельной линии, состоящей из одножильных кабелей, которые охвачены ферромагнитными сердечниками, при двустороннем замыкании собственных экранов. Рассмотрены кабельные линии с укладкой кабелей треугольником и в плоскости. Предложенные соотношения для расчета эффективности экранирования магнитного поля верифицированы экспериментально Отримано компактні співвідношення для розрахунку ефективності екранування магнітного поля високовольтної трифазної кабельної лінії, що складається з одножильних кабелів охоплених феромагнітними осердями, при двосторонньому замиканні власних екранів. Розглянуто кабельні лінії з прокладкою кабелів трикутником і в площині. Запропоновані співвідношення для розрахунку ефективності екранування магнітного поля верифіковано експериментально In this paper we obtain compact expressions for the magnetic field shielding factor of a high-voltage three-phase cable line consisting of single-core cables with two-point bonded cable shields and ferromagnetic cores installed. To obtain these expressions we develop the analytical model of the cable line. Following assumptions are made to develop the model: the current distribution in each cable shield is uniform, cylindrical ferromagnetic cores covering the cables are not magnetized to saturation and their magnetic permeability is constant, each of the ferromagnetic cores is magnetized only by the core current and the shield current of the cable that it covers, the magnetic field inside ferromagnetic cores is axisymmetric, the magnetic field is plane-parallel over the entire cable line. We consider common cases of flat and trefoil cable lines. The proposed expressions for the magnetic field shielding factor are verified experimentally. The physical model is made of three cables of the type NA2XSF(L)2Y-110 1240/70. It is shown that the difference between numerical simulation results and experimental data lays within 15 %.